Operative indicators for drought mitigation tools in multireservoir systems - Sechi G.M.; Sulis A. (Drought management: scientific and technological innovations, 2008)
Although several studies have been done regarding drought indicators and their classification, few of these have focused on how to link operative indicators and drought mitigation measures to manage and plan complex water resource systems in an effective way. In this paper a methodology is presented and applied to the Agri-Sinni water system to aid the water Authority in the decision making process to face droughts. The methodology includes optimization and simulation tools. The optimization model uses indicators as triggers of long and short term measures in a pro-active approach. An additional set of measures could be implemented during particularly serious drought event in the simulation analysis. Results show the usefulness of the proposed approach in defining the best combination of pro-active and reactive measures.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)